Gallbladder lithiasis in gastrectomized patients - Delgado Pereira, Bolívar (Cirugía del Uruguay, 2020)
Work of Prof A Chifflet Clinics. Presented at 8th Congress Brazil of Surgery , Sao Paulo, July 1963